PENGETAHUAN DAN SIKAP TENTANG KESEHATAN REPRODUKSI YANG MENGIKUTI DAN TIDAK MENGIKUTI SUSCATIN (Studi pada Calon Pengantin yang Terdaftar di KUA Kabupaten Grobogan) - Dilla Fitriana Salekha; Sri Achadi Nugraheni; Atik Mawarni (Jurnal Kesehatan Masyarakat, 2019)
Reproductive health is currently the target of the 3rd and 5th objective of sustainable development (SDG) (ensuring healthy living and promoting well-being for all ages; and achieving gender equality and empowering all women and girls). Reproductive health is important to be maintained in an effort to realize the welfare of society and produce a quality generation. The brides are the right target in an effort to improve the health of the period before pregnancy. The bride and groom need to prepare good reproductive health for a quality generation. The aim of this study is to describe the attitudes and knowledge about reproductive health of brides to be in the Grobogan District. The population was all bride in Grobogan District in June – August 2019. The sample was 74 respondents with 37 following suscatin and 37 not following suscatin. The results of this study were most of the respondents who took suscatin and not took suscatin had good knowledge and attitudes about reproductive health.